Estudo da pobreza multidimensional no Brasil : uma análise regional para 2008 - Maciel, Daniel Thomaz Giacomelli Nunes (2015)
This study used a multidimensional poverty measure to Brazil in 2008 to assess the most influential variables in poverty in each region, highlighting the groups in which a higher proportion of vulnerable and thus suggest poverty minimization strategies. The states where there was a higher proportion of vulnerable was Roraima and Maranhão respectively, and the location, education and income had a significant influence in poverty as expected, but variables related to quality of life, such as sedentary lifestyle also had influence . After identified the variables with the largest presence in the poorest and the degree of poverty, the research proposed minimization strategies of poverty based on the literature and viewed by results. Among the strategies suggested are combating food insecurity and child labor by transferring income to those families below the minimum welfare line, along with the fight against indiscriminate belief in the dignity of work early, fighting disparities in access to education and the labor market by certain historical groups, prejudice factor and it influences their income, and therefore in poverty and combat the asymmetry of information, in particular the problem of adverse selection of food protudos. Finally, the survey highlights the most significant variables in each Region.